2009
DOI: 10.1109/jmems.2009.2032784
|View full text |Cite
|
Sign up to set email alerts
|

MEMS Vibration Energy Harvesting Devices With Passive Resonance Frequency Adaptation Capability

Abstract: International audienceFurther advancement of ambient mechanical vibration energy harvesting depends on finding a simple yet efficient method of tuning the resonance frequency of the harvester to match the one dominant in the environment. We propose an innovative approach to achieve a completely passive, wideband adaptive system by employing mechanical nonlinear strain stiffening. We present analytical analysis of the underlying idea as well as experimental results obtained with custom fabricated MEMS devices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 21 publications
3
65
0
Order By: Relevance
“…Nonlinearity in the spring stress-strain relationship can generate either a hardening, [30,31], or a softening behavior, [32,33]. In the first case the resonant frequency increases when the oscillation amplitude increases, Fig.…”
Section: Nonlinear Springsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinearity in the spring stress-strain relationship can generate either a hardening, [30,31], or a softening behavior, [32,33]. In the first case the resonant frequency increases when the oscillation amplitude increases, Fig.…”
Section: Nonlinear Springsmentioning
confidence: 99%
“…Therefore, the electrode lengths and shapes are important parameters that affect the output voltage due to the non uniformity of the strain along the beam [88]. Kim et al have fabricated and compared piezoelectric energy harvesters based on d 31 and d 33 modes [89]. These authors have demonstrated that the output power of the d 33 mode depends strongly on the dimensions of IDE.…”
Section: Piezoelectric Energy Harverstersmentioning
confidence: 99%
“…Marzencki et al, [11] has proposed an energy harvesting device employing the mechanical non linear strain stiffness using a clamped-clamped beam. For such systems the stiffness depends on the amplitude and the frequency of the vibration source.…”
Section: Using Non Linear Springmentioning
confidence: 99%
“…The other method of ensuring that the energy harvester has a self-tuning resonance frequency capability to match the base motion frequency is integrating the harvester with an accelerometer, a displacement sensor, and an actuator to tune the stiffness of the harvester based on the base vibration frequency (Leland & Wright, 2006). Passive frequency-adjusting energy-harvesting mechanisms have grown in use over the past few years (Daminakis et al, 2005;Gu & Livermore, 2010;Lee et al, 2007;Mansour et al, 2010;Marzencki et al, 2009). (Youngsman et al, 2005) presented a model for a frequency-adjustable vibration energy harvester.…”
Section: A Review Of Previous Research On Wide-bandwidth Energy-harvementioning
confidence: 99%